زيادات ابن السُّبْكيّ ومخالفاته في "جَمْع الجَوامِع" على "منهاج الوصول" للبيضاوي فِي مسائل الأمْر : (Ibn al-Subkī’s Additions and Divergences in “Jamʿ al-Jawāmiʿ” from al-Bayḍāwī’s “Minhāj al-Wuṣūl” in Issues Concerning the Imperative (al-Amr)) - إدريس بن أحمد بن سالم المعيني; محمد سعيد بن خليل المجاهد (At-Tajdid - Intellectual Refereed Journal, 2026)
Abstract This study examines the additions and points of divergence introduced by Ibn al-Subkī in Jamʿ al-Jawāmiʿ in relation to al-Bayḍāwī’s Minhāj al-Wuṣūl, focusing specifically on issues concerning the concept of command (al-amr) and its related discussions. Given that both works are regarded as foundational texts in the discipline of uṣūl al-fiqh, there is a clear need to identify and analyse these additions and divergences. The research problem is formulated through the following questions: What additions and divergences did Ibn al-Subkī introduce in Jamʿ al-Jawāmiʿ with respect to al-Bayḍāwī’s Minhāj al-Wuṣūl in matters related to command? What types of additions or divergences are present, and what are the underlying reasons for them? This study aims to address these questions and highlights its significance in facilitating more effective engagement with the two texts, as well as in saving time and effort for students of uṣūl al-fiqh. The study adopts a descriptive, inductive, and comparative methodology. After a thorough examination of the discussions on command in the two works, the study finds that there are six instances of addition, while no cases of divergence were identified in these issues, as all of them represent points uniquely introduced by Ibn al-Subkī in his compilation. The study also clarifies the main types of these additions and their underlying reasons, and outlines the general characteristics of each of the two works. Keywords: Ibn al-Subkī; Jamʿ al-Jawāmiʿ; al-Bayḍāwī; Minhāj al-Wuṣūl; command.